2020
DOI: 10.1590/s1984-29612020024
|View full text |Cite
|
Sign up to set email alerts
|

A new species of Tereancistrum (Monogenea: Dactylogyridae), parasite of Prochilodus lineatus (Characiformes: Prochilodontidae) from southeast Brazil

Abstract: A new species of Tereancistrum Kritsky, Thatcher & Kayton, 1980 collected of Prochilodus lineatus gills from the Batalha River, Tietê-Batalha basin, São Paulo State, Brazil is described. The new species can be distinguished from its congeners mainly by the configuration of the ventral bar, which has an anvil-shaped characteristic with corrugated anterior projection. Tereancistrum takemotoi n. sp. is morphologically similar to T. toksonum Lizama, Takemoto & Pavanelli, 2004 in terms of their dorsal bars … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Concerning ectoparasites, different studies carried out in Maranhão State, as well as in other Brazilian states, have shown that the incidence of these organisms in fish is a common issue, whether in fish farms or the natural environment (Cunha 2015, Rodrigues et al 2017, Fujimoto et al 2019, Leite et al 2020. It is worth emphasizing that parasitism in fish is a challenge, regardless of the season of the year, due to the complexity of factors involved in it, such as the ones inherent to hosts (age, immunological status, intercurrent diseases, among others), parasitic agents (species and pathogenicity) or the environment (climate, local hygiene, biosecurity, reservoirs, among others).…”
Section: Resultsmentioning
confidence: 99%
“…Concerning ectoparasites, different studies carried out in Maranhão State, as well as in other Brazilian states, have shown that the incidence of these organisms in fish is a common issue, whether in fish farms or the natural environment (Cunha 2015, Rodrigues et al 2017, Fujimoto et al 2019, Leite et al 2020. It is worth emphasizing that parasitism in fish is a challenge, regardless of the season of the year, due to the complexity of factors involved in it, such as the ones inherent to hosts (age, immunological status, intercurrent diseases, among others), parasitic agents (species and pathogenicity) or the environment (climate, local hygiene, biosecurity, reservoirs, among others).…”
Section: Resultsmentioning
confidence: 99%